Translation and Cross‐Cultural Adaptation of the Toronto Extremity Salvage Score (TESS) for Latin American Spanish–Speaking Patients With Limb Sarcoma - Oscar Ceballos; Jorge Cabrolier; Begoña Chehade; Francisco Hardoy; Francisco Cortes; Ricardo Tolosa; Orlando Wevar (My University, 2024)
Background and Objectives: This study aims to translate and culturally adapt the Toronto Extremity Salvage Score (TESS) for Latin American Spanish–speaking patients, enhancing the tool’s accessibility for evaluating postsurgical functional outcomes in sarcoma patients across Latin America.Methods: The TESS questionnaires for lower extremity (LE) and upper extremity (UE) were translated and adapted following international guidelines. The process included forward and backward translation, expert committee review, and pretesting with cognitive interviewing. Patients treated for bone or soft tissue tumors in LE or UE were recruited to complete the adapted questionnaires. Test–retest reliability was evaluated by having participants complete the questionnaire again 2 weeks after the initial assessment.Results: A total of 89 participants completed the questionnaires. The study found high internal consistency, with Cronbach’s alpha values reaching 0.9437 for LE and 0.9402 for UE. An agreement rate of 98.4% for the global score of TESS‐LE (95% confidence interval [CI]: 0.909–1.059) and 93.9% for TESS‐UE (95% CI: 0.882–0.995) was observed, demonstrating strong test–retest reliability.Conclusions: The Latin American Spanish version of TESS for both lower and upper extremities is a reliable and culturally appropriate tool for assessing physical function in limb sarcoma patients. Further validation across diverse Latin American populations is encouraged to strengthen its broad applicability.
Keywords: outcomes; sarcoma; tess; translation; adult; aged; bone neoplasms; cross-cultural comparison; female; humans; language; latin america; limb salvage; lower extremity; male; middle aged; reproducibility of results; sarcoma; soft tissue neoplasms; surveys and questionnaires; translations; young adult; adult; aged; bone tumor; cultural factor; ethnology; female; human; language; limb salvage; lower limb; male; middle aged; pathophysiology; publication; questionnaire; reproducibility; sarcoma; soft tissue tumor; south and central america; surgery; young adult